2009
DOI: 10.3350/kjhep.2009.15.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Model for End-stage Liver Disease and hepatic venous pressure gradient for predicting survival in patients with decompensated liver cirrhosis

Abstract: Both MELD and HVPG are independent prognostic factors of death within 3 and 12 months in patients with decompensated liver cirrhosis, and their accuracies are similar. However, HVPG has a limited role in the prediction of death in decompensated cirrhosis due to its invasiveness and limited use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Furthermore, comparison studies between HVPG and MELD score in patients with DC showed different results in the ability to predict long-term mortality. 6 14 15 16 Suk, et al 15 suggested that HVPG in predicting mortality may be more useful than MELD, while other authors showed no additional effect of HVPG on MELD score. 14 16 Our study showed that the discriminative ability of HVPG to predict 1-year, 2-year, and overall mortality was useful, although it was not significantly different from that of the MELD score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, comparison studies between HVPG and MELD score in patients with DC showed different results in the ability to predict long-term mortality. 6 14 15 16 Suk, et al 15 suggested that HVPG in predicting mortality may be more useful than MELD, while other authors showed no additional effect of HVPG on MELD score. 14 16 Our study showed that the discriminative ability of HVPG to predict 1-year, 2-year, and overall mortality was useful, although it was not significantly different from that of the MELD score.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Several studies have found that HVPG values above 16 mm Hg or 18 mm Hg are an important predictor of poor outcome in DC. 2 6 15 In these studies, determining the prognostic value of HVPG was performed at the time of the first manifestation of decompensation. Similarly, we found that an HVPG of 17 mm Hg was the best discriminative cutoff value for the prediction of long-term mortality risk in patients with DC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al10 measured the HVPG in 136 patients with decompensated cirrhosis and found that it was not a significant predictor of mortality. To determine the predictive nature of the HVPG, prospective studies with a broad group of patients (e.g., etiology, sex, and geographic region) are needed.…”
Section: Discussionmentioning
confidence: 99%